U-blade gamma 3 vs. gamma 3 nails for intertrochanteric hip fracture: Meta-analysis - Mariscal, Gonzalo; Lorente, Rafael; Barrios, Carlos (Frontiers in Surgery, 2022)
Background and Objective: Intertrochanteric fracture is a growing problem in the traumatology department. The use of intramedullary devices has increased, representing the first treatment option in intertrochanteric fractures. U-Blade devices appeared to avoid rotation of the femoral head over the femoral neck. The aim of this study was to conduct a meta-analysis of the surgical treatment of intertrochanteric fractures comparing in terms of safety and efficacy the U-Blade Gamma 3 nail versus the conventional Gamma 3 nail. Methods: A literature search for intertrochanteric fracture 31A1-31A3 according to the AO/OTA classification was performed. Baseline characteristics of each article were obtained, radiological outcomes were TAD, sliding distance (mm), cut-out rate and lateralization rate. Surgery time (min) was also recorded. A meta-analysis was performed with Review Manager 5.4. Results: Five retrospective studies were included. Respect to TAD and sliding distance there were no differences between two groups (MD 0.47, 95% CI -0.46 to 1.40) and (MD 0.39, 95% CI 0.13 to 0.66). The cut-out rate and lateralization rate did not show differences between two groups (p0.05). Finally, the surgery time was significantly higher in the U-Blade Gamma 3 group (MD -4.84, 95% CI -7.22 to -2.46). Conclusions: The use of U-Blade Gamma 3 did not show significant differences in the radiological results compared with the conventional Gamma 3 nail.